Examination on implications of Web 2.0 Tools in the field of Special Education //Examen sobre las implicaciones de las herramientas Web 2.0 en el campo de la educación especial - Kanbul, Sezer; Soykan, Emrah; Erçağ, Erinc (Revista de la Universidad del Zulia, 2020)
AbstractThe objective of this article is to analyze the published studies that bear the title Web 2.0 in the field of special education. For this, the electronic databases IEEE Xplore, ScienceDirect, SpringerLink, Taylor & Francies Online, Wiley and the search engine Google Scholar were scanned in order to locate articles titled Web 2.0. Nineteen articles were selected from the 1220 articles found in the field of special education, and they were analyzed using the content analysis technique. Data were collected using the "Article Publication Form" developed by the researchers. The data obtained in the study were interpreted based on percentage and frequency. The results obtained are believed to lead to further studies.Resumen El objetivo de este artículo es analizar los estudios publicados que llevan el título Web 2.0 en el campo de la educación especial. Para ello, se escanearon las bases de datos electrónicas IEEE Xplore, ScienceDirect, SpringerLink, Taylor & Francies Online, Wiley y el motor de búsqueda Google Scholar a fin de ubicar artículos titulados Web 2.0. Diecinueve artículos fueron seleccionados de los 1220 artículos que se encontraron en el campo de la educación especial, y fueron analizados mediante la técnica de análisis de contenido. Los datos se recopilaron con el "Formulario de publicación de artículos" desarrollado por los investigadores. Los datos obtenidos en el estudio se interpretaron en base a porcentaje y frecuencia. Se cree que los resultados obtenidos darán lugar a más estudios.